Brain damage and personhood: a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Philosophy at Massey University - Mackenzie, Anne Jennifer (Massey University, 1991)
In certain cases of specific brain-damage, neurologists are often puzzled about the patient's status as a person. They suggest that the person is changed, diminished, or even absent, but it is not clear why. Can a philosophical account of personhood help answer their questions? My aim is to show that a philosophical understanding of personhood can be improved by taking account of actual cases of brain-damage. At the same time, a philosophical analysis enriched in this way can help to dispel uncertainty and perplexity concerning those cases. I outline a necessary condition of personhood and show reasonable justification for it. The condition combines the notions of consciousness, being a continuing subject of experience, and awareness of being such a subject. Assuming the condition is justified, I go on to consider its application. I suggest that cases of very specific brain-damage may provide clues to capacities which are essential if the condition is to be satisfied. A closer examination of what must be the case if an individual satisfies each of the parts of the condition shows that this is difficult to determine. The main part of my project has two sections. Firstly, I focus on the condition itself. I show that memory for experiences is essential for having a sense of oneself as a continuing subject of experience and I answer possible objections to this claim. Memory alone is insufficient, for the memories need to be processed into something like a narrative. This processing calls for a basic linguistic capacity and so this capacity is also necessary if the condition is to be satisfied. In the second part of my project, I select accounts of brain-damage described in the literature. I choose seven cases where experiential memory is impaired, one case where linguistic capacity is lost, and one case of profound deafness where linguistic capacity did not develop until quite late. A final case is an example of very severe brain-damage where minimal memory and linguistic capacity were recovered while much else remained lost. Considering these two parts together, I point out how the philosophical analysis can help us to understand just what it is that the patients have lost. At the same time, the case studies show that the sense of self is diminished when there are specific memory and linguistic deficits. The patients, despite being mobile, articulate and intelligent, cannot function as persons in many respects. Their difficulties support my claims about the necessity of memory and linguistic capacity. Further support comes from the case where memory and linguistic capacity are recovered to some extent in the face of devastating losses. Overall I try to show that a philosophical analysis of the concept of a person will be enhanced if we take note of cases of specific brain damage. We can gain insights from sympathetic accounts of the lives of these patients and an enhanced philosophical account can contribute to our understanding of the plight of the brain-damaged.
Keywords: Identity (Psychology); Self